Bone marrow mesenchymal stem cell-derived extracellular vesicle infusion for amyotrophic lateral sclerosis - Crose, Joshua J; Crose, Arezou; Ransom, John T; Lightner, Amy L (Neurodegenerative disease management, 2024)
In this pilot safety study, we hypothesized that a human bone marrow stem cell-derived extracellular vesicle (hBM-MSC EV) investigational product (IP) would be safe and exhibit potential efficacy in amyotrophic lateral sclerosis (ALS) patients. Ten ALS patients received two 10-ml intravenous infusions of the IP given 1 month apart and evaluated over 3 months. There were no serious adverse events or adverse events related to the IP and 30% of subjects' ALS functional rating scale-revised (ALSFRS-R) scores did not decline. HBM-MSC EVs appear safe in ALS patients. This early investigation suggests a controlled study of EVs for the treatment of ALS is warranted.